Antibacterial And Antioxidant Activities Of The Essential Oils And Phenolic Extracts Of Myrtus Communis And Zygophylum Album From Algeria - Belmimoun, A.; Meddah, B.; Meddah, A.t.; Sonnet, P. (University of Eloued جامعة الوادي, 2016)
The present study deals with the evaluation of the in vitro antioxidant and antibacterial activity of phenolic extracts and essential oils of two medicinal and aromatic plants Zygophyllum album and Myrtus communis by using the 2,2- diphenyl-2-picrylhydrazyl radical ,total antioxidant power and agar diffusion methods and minimum inhibitory concentration (MIC) determination. Moreover, the extracts were investigated for their polyphenolic, flavonoids, tannins and anthocyans content by using the Folin-Ciocalteu assay, the aluminium trichlorid method, reaction with vanillin and colometer method based on differentiation of absorbance, respectively. The results showed that the highest antioxidant capacity was exhibited by the aqueous extract of Myrtus communis with IC50= 29,080mg/ml. All extracts possessed more or less antibacterial activity against the tested Gram- positive and Gram –negative bacteria Bacillus subtilis and E.coli were the more susceptible microorganisms to all extracts and essential oils. Pronounced antibacterial activity was observed by the methanolic extract of Zygophylum album (MIC value=25 µg/ml). Morever, the results showed that the phenolic compounds and flavonoids were abundant in Myrtle aqueous extracts.
Articale in Journal of fundamental and Applied Sciences Vol. 08, N. 02
Keywords: antimicrobial; antioxidant; plant; essential oil; phenolic extract.